Extreme temperatures and cardiovascular mortality: assessing effect modification by subgroups in Ganzhou, China - Wei Zhang; Gang Du; Liang Xiong; Tingting Liu; Zuobing Zheng; Qiong Yuan; Jiahui Yang; Yangna Wu; Rongfei Zhu; Gonghua Hu (Taylor & Francis Group, 2021)
Background Many people die from cardiovascular diseases each year, and extreme temperatures are regarded as a risk factor for cardiovascular deaths. However, the relationship between temperature and cardiovascular deaths varies in different regions because of population density, demographic inequality, and economic situation, and the evidence in Ganzhou, China is limited and inconclusive. Objective This study aimed to assess extreme temperature-related cardiovascular mortality and identify the potential vulnerable people. Methods After controlling other meteorological measures, air pollution, seasonality, relative humidity, day of the week, and public holidays, we examined temperature-related cardiovascular mortality along 21 lag days by Poisson in Ganzhou, China. Results A J-shaped relationship was observed between mean temperature and cardiovascular mortality. Extremely low temperatures substantially increased the relative risks (RR) of cardiovascular mortality. The effect of cold temperature was delayed by 2-6 days and persisted for 4-10 days. However, the risk of cardiovascular mortality related to extremely high temperatures was not significant (p > 0.05). Subgroup analysis indicated that extremely low temperatures had a stronger association with cardiovascular mortality in people with cerebrovascular diseases (RR: 1.282, 95% confidence interval [CI]: 1.020-1.611), males (RR: 1.492, 95% CI: 1.175-1.896), married people (RR: 1.590, 95% CI: 1.224-2.064), and people above the age of 65 years (RR: 1.641, 95% CI: 1.106-2.434) than in people with ischemic heart disease, females, unmarried people, and the elderly (≥65 years old), respectively. Conclusions The type of cardiovascular disease, sex, age, and marital status modified the effects of extremely low temperatures on the risk of cardiovascular mortality. These findings may help local governments to establish warning systems and precautionary measures to reduce temperature-related cardiovascular mortality.